A metal–organic framework functionalized with piperazine exhibiting enhanced CH4 storage. Issue 1 (2nd December 2016) - Zhang, Mingxing; Chen, Cong; Wang, Qian; Fu, Wensheng; Huang, Kunlin; Zhou, Wei
Abstract : NJU-Bai 19, the first cycloaliphatic ring (piperazine) functionalized MOF-505 analogue, exhibits a notably high methane storage capacity of 246 cm 3 (STP) cm −3 (at room temperature and 65 bar) and a working capacity of 185 cm 3 (STP) cm −3 . Abstract : NJU-Bai 19, the first cycloaliphatic ring (piperazine) functionalized MOF-505 analogue, exhibits a notably high methane storage capacity of 246.4 cm 3 (STP) cm −3 (at room temperature and 65 bar); this is 93.6% of the new volumetric target of the US Department of Energy if the packing density loss is ignored. Compared with NOTT-101, when piperazine groups are inserted, the methane uptake capacity ofNJU-Bai 19 at 65 bar and RT can be significantly enhanced with lower Q st . A relatively low increase was also observed in the uptake at 5 bar. Thus it has a much higher methane storage working capacity (deliverable amount of methane between 65 and 5 bar) of 185 cm 3 (STP) cm −3 compared with NOTT-101 (174 cm 3 (STP) cm −3 ). When the temperature was decreased from 298 to 273 K at working pressures between 65 bar and 5 bar, the volumetric CH4 working capacity ofNJU-Bai 19 is almost unchanged (from 185 to 189 cm 3 (STP) cm −3 ), while some of the famous MOFs with high Q st showed a decrease with a decrease in temperature. The combination of the balanced porosity and framework density and the lipophilic surface is considered to result in the increased methane storage and working capacities.